Enhanced crystallization resistance and thermal stability via suppressing the metastable superlattice phase in Ni-(Pd)-P metallic glasses. (1st April 2020) - Du, Qing; Liu, Xiongjun; Cao, Yihuan; Wen, Yuren; Xiao, Dongdong; Wu, Yuan; Wang, Hui; Lu, Zhaoping
Abstract: Virtually, glass formation is to avoid crystallization during solidification, i.e., a consequence of the competition between the undercooled liquid and primary crystalline phases. It is found that the crystallization resistance of the binary Ni-P system was drastically enhanced with alloying of Pd and correspondingly, the critical size for glass formation increased significantly from the micrometer to millimeter scale. Thermodynamically, the introduction of Pd could effectively increase the atomic size mismatch and heat of mixing, which are beneficial to stabilize the supercooled liquid. Kinetically, the introduction of Pd not only successfully suppresses the formation of metastable superlattice phase, which is prone to nucleation and growth in the supercooled liquid state, but also changes the crystallization mechanism from the primary to eutectic mode. The current finding sheds light on understanding glass formation of the most studied Pd-Ni-P system and the glass-forming ability in general.